SPECIFIC CHARACTERISTICS OF ORAL SPEECH DEVELOPMENT OF YOUNG STUDENTS - Saida Tursunova; Donayeva Ashuroy (Scholar Express Journals, 2023)
The development of speech in children is a process of great importance for their future. This process goes through different stages in every child. And this depends on their psychology in the family environment and the education they receive in the school process. This article talks about the concept of speech, the methodology of speech development, its importance, ways of developing students' speech, methodology, a number of aspects of speech acquisition, directions of speech development, clearly defined requirements for the development of students' speech, life skills that must be formed in students by achieving speech development in the process of education.
Keywords: Speech; education; methodology